2002
DOI: 10.1124/mol.61.5.989
|View full text |Cite
|
Sign up to set email alerts
|

l-Acetylcarnitine Induces Analgesia by Selectively Up-Regulating mGlu2 Metabotropic Glutamate Receptors

Abstract: L-Acetylcarnitine (LAC, 100 mg/kg, s.c.), a drug commonly used for the treatment of painful neuropathies, substantially reduced mechanical allodynia in rats subjected to monolateral chronic constriction injury (CCI) of the sciatic nerve and also attenuated acute thermal pain in intact rats. In both cases, induction of analgesia required repeated injections of LAC, suggesting that the drug induces plastic changes within the nociceptive pathway. In both CCI-and sham-operated rats, a 24-day treatment with LAC inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
95
0
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 104 publications
(103 citation statements)
references
References 39 publications
7
95
0
1
Order By: Relevance
“…Western blot analysis of mGlu receptor proteins was carried out as described previously 44 using polyclonal antibodies against mGlu1a, mGlu4, mGlu5, mGlu6, mGlu7, mGlu8 (Upstate Technology) and mGlu2/3 (Chemicon International, Temecula, CA, USA) receptors. 3 H]inositol phosphates accumulating during the reaction was measured as described previously.…”
Section: Western Blot Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Western blot analysis of mGlu receptor proteins was carried out as described previously 44 using polyclonal antibodies against mGlu1a, mGlu4, mGlu5, mGlu6, mGlu7, mGlu8 (Upstate Technology) and mGlu2/3 (Chemicon International, Temecula, CA, USA) receptors. 3 H]inositol phosphates accumulating during the reaction was measured as described previously.…”
Section: Western Blot Analysismentioning
confidence: 99%
“…44 The following primers were used for each metabotropic glutamate receptor subtype indicated below: mGlu1: forward GCTGTA CCTACTATGCCTTC, reverse AGACCATGACACAGACTTGC; mGlu2: forward CTACAGTGATGTCTCCATCC, reverse AAAGCCTCAATGCCT GTCTC; mGlu3: forward CAAGTGACTACAGAGTGCAG, reverse CTGTC ACCAATGCTCAGCCTC; mGlu4: forward CCAACGAGGATGACATCA GG, reverse CACAGGTCACGGTGCATGG; mGlu5: forward GTCCTTCT GTTGATCCTGTC, reverse ATGCAGCATGGCCTCCACTC; mGlu6: forward GCCAGTCAGATGATTCCACC, reverse GCCTGGTACCTGGAA GATGTC; mGlu7: forward CCAGATGTGGCAGTGTGTTC, reverse CGA GTCTTGATGGCATACAC; mGlu8: forward ATCACCTTCAGCCTCATC TC, reverse TGTGACCACAGCCTTGAAGC.…”
Section: Rt-pcr Analysismentioning
confidence: 99%
“…Indirect activation of muscarinic receptors as well as the activation of the PLC-IP 3 pathway has been postulated to mediate the antinociceptive effect of L-acetylcarnitine in experimental models of acute pain [14,15]. Moreover, increased expression of metabotropic glutamate receptor 2 (mGlu2) in regions of the nervous system involved in pain transmission after chronic administration of L-acetylcarnitine has been proposed to account for the antinociceptive efficacy of the drug in acute pain and in chronic pain after nerve injury in rats [7]. In vitro studies performed in cultured DRG neurons showed that the increased expression of mGlu2 receptors occurs mainly in the large diameter neurons from which large myelinated Abeta fibers originate [8].…”
Section: Effects Of L-acetylcarnitine In Experi-mental Models Of Acutmentioning
confidence: 99%
“…The antinociceptive effect of L-acetylcarnitine has been shown in different pain models in rodents [7,14,15], and several mechanisms have been proposed. Indirect activation of muscarinic receptors as well as the activation of the PLC-IP 3 pathway has been postulated to mediate the antinociceptive effect of L-acetylcarnitine in experimental models of acute pain [14,15].…”
Section: Effects Of L-acetylcarnitine In Experi-mental Models Of Acutmentioning
confidence: 99%
“…More recently it has been reported that ALCAR induces antinociception by a central indirect cholinergic mechanism (Ghelardini et al, 2002). An up-regulation of mGlu2 receptors in ALCAR-treated animals has also been postulated (Chiechio et al, 2002). Literature data reported that the metabolic intracellular events induced by the activation of the muscarinic system are blocked not only by scopolamine, but also by the Glu2 receptor antagonist LY341495 (Johnson et al, 2000), indicating the presence of a correlation between the glutamatergic and muscarinic system, being the muscarinic system activation downstream to the mGlu2 receptors upregulation.…”
Section: Introductionmentioning
confidence: 99%